Novel plant inducers of PXR-dependent cytochrome P450 3A4 expression in HepG2 cells - Mohammed S. Al-Dosari; Mohammad K. Parvez (Saudi Pharmaceutical Journal)
The cytochrome P450 3A4 (CYP3A4) is the most abundant CYP450 enzyme involved in the metabolism of endogenous products and xenobiotics, including prescription drugs and herbals. Modulation of hepatic CYP3A4 gene expression via nuclear receptors, like pregnane X receptor (PXR), is a major cause of adverse effects like drug-unresponsiveness and toxicity. In the present study, ethanol extracts of 58 medicinal plants, belonging to 27 families, were evaluated for potential activities in CYP3A4 induction in HepG2 cells by reporter gene assay. For PXR-mediated CYP3A4 induction, a 50 μg/ml concentration was used for all non-cytotoxic plants extracts. Rifampicin (10 μM) and DMSO (0.1%) were used as standard inducer and untreated (negative) control, respectively. The comparative fold-induction of CYP34A by the plant extracts in relation to the untreated control was determined. As a result, Dodonaea angustifolia (2.62 fold; P < 0.0001) was found to be the most promising inducer of CYP3A4, followed by Euphorbia tirucalli (1.95 fold; P = 0.0004), Alternanthera pungens (1.74 fold, P = 0.0035), and Ficus palmata (1.65 fold; P = 0.0097). Further phytochemical characterizations of the active plants are therefore, warranted. Keywords: Pregnane X receptor, Cytochrome P450, CYP3A4, Plant extracts, Luciferase